2018
DOI: 10.1556/030.65.2018.047
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mRNA expression of members of TGFB1-associated pathways in human leukocytes during EBV infection

Abstract: Transforming growth factor β 1 (TGFB1) likely contributes to the pathogenesis of Epstein-Barr virus (EBV)-mediated cancer. A microarray containing 59 probes for detecting mRNA of members of TGFB1-associated pathways was developed. mRNA expression of TGFB1 receptors and members of connected pathways were examined in peripheral blood leukocytes of patients during acute EBV infection and after recovery. TGFB1 and TGFBR2 mRNA expression was increased in patients with EBV infection. Similarly, mRNA expression of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In fact, in previous studies, the targeted regulatory interaction of miR-663a and TGFB1 has been demonstrated (Zhang et al, 2018). Moreover, numerous studies have previously revealed that changes in TGFB1-regulated signalling have pivotal influences on viral infections, such as Epstein-Barr virus (EBV) (Filatova et al, 2019), respiratory syncytial virus (RSV) (Xu et al, 2020), and COVID-19 (Vaz de Paula et al, 2021), thereby suggesting that the upstream regulatory molecule miR-663a of TGB1 may directly affect the infection process of these viruses. Additionally, miR-4286 is believed to have a tumour promoter role in the progression of numerous cancers, including non-small cell lung cancer (An et al, 2019), gastric cancer (Tsai et al, 2020), and prostate cancer (Li et al, 2019), but whether miR-4286 has a vital role in virus infection remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in previous studies, the targeted regulatory interaction of miR-663a and TGFB1 has been demonstrated (Zhang et al, 2018). Moreover, numerous studies have previously revealed that changes in TGFB1-regulated signalling have pivotal influences on viral infections, such as Epstein-Barr virus (EBV) (Filatova et al, 2019), respiratory syncytial virus (RSV) (Xu et al, 2020), and COVID-19 (Vaz de Paula et al, 2021), thereby suggesting that the upstream regulatory molecule miR-663a of TGB1 may directly affect the infection process of these viruses. Additionally, miR-4286 is believed to have a tumour promoter role in the progression of numerous cancers, including non-small cell lung cancer (An et al, 2019), gastric cancer (Tsai et al, 2020), and prostate cancer (Li et al, 2019), but whether miR-4286 has a vital role in virus infection remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%